Archduke Ferdinand’s Musical Parnassus in Graz - Kokole, Metoda (De musica disserenda, 2017)
Archduke Ferdinand of Inner Austria was not only the dedicatee of the anthology Parnassus Musicus Ferdinandaeus – in itself a rich document of the future Holy Roman Emperor’s wide-ranging musical connections – but his court in Graz also became – on account of his personal music interests and the opportunities provided by carefully planned family connections – a major hub of the leading musical trends of the first two decades of the seventeenth century. The paper provides an overview of this intricate web forming Ferdinand’s musical “Parnassus” in Graz.